Bridge deck analysis - O'Brien, Eugene J.; Keogh, Damien L.; O'Connor, Alan J. (CRC Press, 2015)
The new edition introduces reliability analysis, an emerging area that allows bridge engineers to assess risk when maintaining older or damaged bridges in service.